2018
DOI: 10.1186/s12864-018-4574-4
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of Aspergillus tubingensis G131 and overview of its secondary metabolism potential

Abstract: Background: Black Aspergilli represent one of the most important fungal resources of primary and secondary metabolites for biotechnological industry. Having several black Aspergilli sequenced genomes should allow targeting the production of certain metabolites with bioactive properties. Results: In this study, we report the draft genome of a black Aspergilli, A. tubingensis G131, isolated from a French Mediterranean vineyard. This 35 Mb genome includes 10,994 predicted genes. A genomic-based discovery identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 63 publications
(138 reference statements)
2
30
0
Order By: Relevance
“…A. tubingensis G131 was provided by École Nationale Supérieure Agronomique de Toulouse (France); this fungus is non-mycotoxigenic as the synthetic genes required for the production ochratoxin A and fumonisin are absent from its genome [14]. It was conserved at 4 • C in a 15 mL bottle on potato dextrose agar (PDA).…”
Section: Fungal Materialsmentioning
confidence: 99%
“…A. tubingensis G131 was provided by École Nationale Supérieure Agronomique de Toulouse (France); this fungus is non-mycotoxigenic as the synthetic genes required for the production ochratoxin A and fumonisin are absent from its genome [14]. It was conserved at 4 • C in a 15 mL bottle on potato dextrose agar (PDA).…”
Section: Fungal Materialsmentioning
confidence: 99%
“…In non-ochratoxigenic strains of A. niger, a 21-kb deletion in a remnant of the polyketide sinthase gene of the putative OTA cluster has been identified (Andersen et al, 2011). In the same way, the genome analysis of A. tubingensis revealed that it does not contain an orthologue of this gene (Choque et al, 2018). In previous studies, we resequenced the genome of three atypical and unique non-OTA producing strains of A. carbonarius (Cabañes et al, 2015;Castellá et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…The most abundant species isolated from our raisin samples was A. tubingensis, including both samples highly contaminated by OTA (Table 1). Although several authors previously declared the ochratoxigenic potential of A. tubingensis strains [24,28,72], the recent genomic analysis of this species revealed the absence of genes responsible for OTA production [73]. Thus, A. tubingensis cannot be a source of OTA contamination in our dried vine fruit samples.…”
Section: Ochratoxigenic and Fumonisins Production Potential Of Aspergmentioning
confidence: 81%